Circulating and tissue biomarkers as predictors of bromine gas inhalation. Issue 1 (9th July 2020) - Juncos, Juan Xavier Masjoan; Shakil, Shazia; Ahmad, Aamir; Aishah, Duha; Morgan, Charity J.; Dell'Italia, Louis J.; Ford, David A.; Ahmad, Aftab; Ahmad, Shama
Abstract: The threat from deliberate or accidental exposure to halogen gases is increasing, as is their industrial applications and use as chemical warfare agents. Biomarkers that can identify halogen exposure, diagnose victims of exposure or predict injury severity, and enable appropriate treatment are lacking. We conducted these studies to determine and validate biomarkers of bromine (Br2 ) toxicity and correlate the symptoms and the extent of cardiopulmonary injuries. Unanesthetized rats were exposed to Br2 and monitored noninvasively for clinical scores and pulse oximetry. Animals were euthanized and grouped at various time intervals to assess brominated fatty acid (BFA) content in the plasma, lung, and heart using mass spectrometry. Bronchoalveolar lavage fluid (BALF) protein content was used to assess pulmonary injury. Cardiac troponin I (cTnI) was assessed in the plasma to evaluate cardiac injury. The blood, lung, and cardiac tissue BFA content significantly correlated with the clinical scores, tissue oxygenation, heart rate, and cardiopulmonary injury parameters. Total (free + esterified) bromostearic acid levels correlated with lung injury, as indicated by BALF protein content, and free bromostearic acid levels correlated with plasma cTnI levels. Thus, BFAs and cardiac injury biomarkers can identify Br2 exposure and predict the severity of organ damage. Abstract : Our results make a case for the use of 2‐bromopalmitic and 2‐bromostearic acids as biomarkers for cardiopulmonary toxicity following exposure to Br2 . These findings are particularly significant because there are no known biomarkers for Br2 exposure. We further provide evidence that the Br2 inhalation biomarker content corresponds to the severity of the injury and that these biomarkers may serve as a tool for the first responders to identify, stratify, and prioritize emergency care for exposed individuals within hours of a mass casualty situation.